The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1167/iovs.12-10281
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Role of the Wnt Signaling Pathway Activation In Laser-Induced Choroidal Neovascularization

Abstract: PURPOSE. Choroidal neovascularization (CNV) is a severe complication of AMD. The Wnt signaling pathway has been shown to mediate angiogenesis. The purpose of this study was to investigate the pathogenic role of the Wnt pathway in CNV and explore the therapeutic potential of a novel Wnt signaling inhibitor in CNV.METHODS. Adult rats and mice were photocoagulated using diode laser to induce CNV. On the same day, the animals were intravitreally injected with a monoclonal antibody (Mab2F1) blocking LRP6 or nonspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 34 publications
5
72
0
Order By: Relevance
“…Therefore, attenuation of the Wnt/β-catenin pathway may be a potential strategy for treating CNV. Monoclonal antibody (Mab)2F1, a novel inhibitor of the canonical Wnt pathway, has been demonstrated to suppress the hypoxia-induced activation of Wnt signaling in cultured RPE cells, thereby ameliorating CNV (27). Similar to the role of Mab2F1 in RPE cells under hypoxic conditions, in the present study, it was demonstrated that knockdown of DKK2 inhibited the hypoxia-induced expression of β-catenin in RPE cells.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, attenuation of the Wnt/β-catenin pathway may be a potential strategy for treating CNV. Monoclonal antibody (Mab)2F1, a novel inhibitor of the canonical Wnt pathway, has been demonstrated to suppress the hypoxia-induced activation of Wnt signaling in cultured RPE cells, thereby ameliorating CNV (27). Similar to the role of Mab2F1 in RPE cells under hypoxic conditions, in the present study, it was demonstrated that knockdown of DKK2 inhibited the hypoxia-induced expression of β-catenin in RPE cells.…”
Section: Discussionsupporting
confidence: 67%
“…A key regulator of this pathway is intracellular β-catenin, which is a transcription coactivator (26). It has been reported that the aberrant upregulation of the Wnt/β-catenin signaling pathway at multiple levels, including Wnt ligands, low-density lipoprotein receptor-related protein 6 and β-catenin, has been observed in laser-induced CNV models (27). In addition, nuclear β-catenin regulates gene transcription by interacting with Wnt target and activator genes (T-cell factor-1/lymphoid enhancer binding factor-1) and knockdown of HIF-1α inhibits the hypoxia-increased accumulation of β-catenin in the nucleus (28).…”
Section: Discussionmentioning
confidence: 99%
“…All of these genes are potent proangiogenic genes associated with ocular angiogenesis. FZD4 is a receptor for Wnt signaling, which is a highly conserved angiogenic pathway activated in both OIR and laser-induced CNV models (16,33,34). On the other hand, Dll4/Notch signaling controls vessel sprouting and branching, and inhibition of DLL4 showed reduced pathological neovessels in OIR (35).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Recently, the Wnt pathway has been suggested to be a pathogenic mechanism of AMD, especially nAMD. 8 The therapeutic effects of Wnt inhibitors, such as monoclonal antibodies to Wnts, have been demonstrated in a mouse model of wet AMD. 8 However, others reported that increased Wnt signaling in light-induced retinal degeneration plays a role in retinal protection.…”
mentioning
confidence: 99%
“…8 The therapeutic effects of Wnt inhibitors, such as monoclonal antibodies to Wnts, have been demonstrated in a mouse model of wet AMD. 8 However, others reported that increased Wnt signaling in light-induced retinal degeneration plays a role in retinal protection. 7,12 They suggested that upregulated Wnt signaling in Müller glia during retinal degeneration could be a protective mechanism to prevent further photoreceptor injury.…”
mentioning
confidence: 99%